2014
DOI: 10.1093/humupd/dmu057
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of saline infusion sonography in the evaluation of uterine cavity abnormalities prior to assisted reproductive techniques: a systematic review and meta-analyses

Abstract: SIS is a highly sensitive investigative modality and comparable to the gold standard tool, hysteroscopy in the detection of intrauterine abnormalities in subfertile women. SIS is a highly sensitive and specific test in the diagnosis of uterine polyps, submucous myomas, uterine anomalies and intrauterine adhesions and can be used as a screening tool for subfertile patients prior to IVF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 56 publications
1
57
2
3
Order By: Relevance
“…This is one of the few systematic reviews and meta-analyses examining the diagnostic accuracy of SCSH in women of reproductive age with AUB. In the literature, there are a considerable number of studies examining the accuracy of this test in patients with AUB, but the analyzed populations are heterogeneous, including postmenopausal women or women with infertility 19,20 . The study that most closely resembles the present analysis was a systematic review by Farquhar et al in 2003 21 , in which the primary objective was to determine the diagnostic accuracy of transvaginal ultrasound, SCSH and hysteroscopy in the investigation of AUB.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the few systematic reviews and meta-analyses examining the diagnostic accuracy of SCSH in women of reproductive age with AUB. In the literature, there are a considerable number of studies examining the accuracy of this test in patients with AUB, but the analyzed populations are heterogeneous, including postmenopausal women or women with infertility 19,20 . The study that most closely resembles the present analysis was a systematic review by Farquhar et al in 2003 21 , in which the primary objective was to determine the diagnostic accuracy of transvaginal ultrasound, SCSH and hysteroscopy in the investigation of AUB.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of SIS remained high when analysed separately for individual pathologies such as endometrial polyps, submucous myomas, intrauterine adhesions and congenital uterine anomalies. It is also suggested that SIS can be considered as an alternative to hysteroscopy as the specificity reaches close to 100 % in detecting intrauterine adhesions, uterine anomalies, endometrial polyps and submucous myomas [15].…”
Section: Diagnosismentioning
confidence: 99%
“…Compared to hysteroscopy, SHG has 87.5% sensitivity, 100% specificity, 100% positive predictive value and 91.6% negative predictive value for the detection of uterine cavity abnormality [11] .…”
Section: Transvaginal Sonography (Tvs)mentioning
confidence: 99%